High Performance Sports - Ottesen TD; Rutland EA; Naushad N; Stratton CSM; Ona Ayala KE; Li X; Tuakli-Wosornu YA (Deutsche Zeitschrift für Sportmedizin)
Problem: Sports provide health-related benefits but also confer risk of both accidental (unintentional) and non-accidental (intentional) injuries. Compared to non-disabled athletes, athletes with impairment (Para athletes) are particularly vulnerable to both unintentional and intentional injuries. Despite increasing global Para sport participation, there is a dearth of injury epidemiology scholarship in this group. This literature gap complicates efforts to assess risk factors and develop injury prevention strategies. Methods: Published injury epidemiology literature in Para athletes was reviewed. Unintentional injuries were defined as unplanned and resulting from accidents or overuse; intentional injuries were defined as harmful maltreatment (eg, bullying, harassment, abuse, and all other forms of intentional violence). Results: Literature on unintentional injury epidemiology in Para athletes is limited, but suggest injury incidence is higher in winter compared to summer Para sports (at the elite level). Ambulant Para athletes are more susceptible to lower extremity injury when compared to seated Para athletes, but overall, the upper extremity is the most commonly injured anatomic region in this group. Literature on intentional injury is similarly scant, but data indicate Para athletes may be up to four times more likely to experience intentional violence in sport compared to non-disabled peers. Discussion: Para athletes are significantly more likely to suffer intentional violence when compared to non-disabled athletes. Conclusions are limited by the paucity of studies. Broader population-level research is needed to better understand risk factors and injury prevention strategies. KEY WORDS: Sports Injury Epidemiology, Para Athletes, Intentional Violence, Injury Prevention